The Accession Negotiations of the Czech Republic to the European Union: how successful? (Czech Journal of International Relations, 2004)
the European Union (1998-2000). The main research questions are: how tomeasure success or failure in the accession negotiations? Are the conditionsof the Czech Republic's entry well negotiated? Why are the results of thenegotiations the way they are? The study demonstrates that the abilities ofnegotiators influence the results of the accession negotiations. Thisconfirms the hypothesis that negotiators' abilities, their strategy, and tacticsmatters in this specific and highly asymmetric negotiations, although thecharacter of the accession negotiations would presume that those shouldhave only minor role in the accession talks. The analysis studies theinfluence of the negotiators' abilities in the good results in the area of thetransitional periods as well as in the relatively less successful outcomes inthe financial deal. Although a direct correlation between the effectivestrategy/tactics and successful results as well as between the incompetentor missing strategy/tactics and unsuccessful outcomes was not found, thestudy proves the impact of the individual as well as collectivestrategy/tactics of the candidates. The Czech Republic individually, as wellas in the cooperation with other candidates, achieved not only expectedminor concessions but was also able to change the original position of theEU and even the EU methodology. The strategy of the Czech foreign policytowards the bilateral disputes with the member states (nuclear powerTemelín, Benes decrees) could influence the low sum of the future Czechincome for the years 2004-2006 from the EU budget, although the resultantamount was mainly determined by the objective reasons in the distributionof the finances among the candidates.